Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Produk Halal Bakery Shop Di Samarinda - Parlina, Tika; Tikawati, Tikawati; Urrahmah, Syifa (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2024)
Choosing Halal Products is a new lifestyle trend in a country with a predominant Muslim population. Samarinda is one of the most promising regions for the introduction of halal culinary products, particularly bread products. Every entrepreneur must comprehend consumer behavior and all the factors that influence purchasing decisions, as well as endeavor to develop and create products with distinct advantages over rivals and pay more attention to taste and the use of high-quality ingredients. Rarely has research been conducted on the factors that influence the decision to purchase halal bakery products. This study aims to add to previous research by focusing on consumer behavior when purchasing halal bakery products. This form of research is quantitative and employs a causal-associational methodology. This study's population consists of Samarinda consumers of Certified Halal Bakery Bread Products. Sampling technique is purposive sampling, with samples of as many as 100 respondents using the Lemeshow formula. Utilizing Google forms for the distribution of questionnaires to collect data. Techniques for data analysis using SmartPls version 3.0. The results indicated that Brand variables and Price variables have no influence on purchasing decisions, whereas Product Innovation variables and Cite preference variables have a significant influence on purchasing decisions.